Policy Adequacy in Delegating Several Authorities to Sub-District Head to Improve the Quality of Waste Management Services at Tangerang Regency Banten Province - Aziz Gunawan (Institut Pemerintahan Dalam Negeri (IPDN), 2017)
This research aims to analyzing adequacy policy of delegating in part of authority deeply and also developing the relevant model. This research is using descriptive design with qualitative approach. Research informant are cleanliness and landscaping agency head, Sub-district head of Cikupa, Sub-district head of Kelapa Dua, Indonesia Clerical Council head and society. Data collecting technique are observation, interview, and documentation. Data is analyzed in descriptive method. Research result shows that adequacy policy of delegating in part of authority to sub-district head in improving the service quality of waste management in Tangerang regency as shows that decreasing of policy cost and increasing of policy effectiveness. Based on these research, developed adequacy model of delegation in part of authority in improving the service quality of waste management at Tangerang regency. These model is theoretical enrichment of Dunn’s adequacy policy theory especially in the third quadrant namely the changing of policy effectiveness and the changing of policy cost. It is different with Dunn’s adequacy policy model which is not focusing in the third quadrant as adequacy policy, this model shows that adequacy policy in the third quadrant namely the changing of policy cost and the changing of policy effectiveness.